2021
DOI: 10.1111/ijcp.14513
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the analgesic effects of two quadratus lumborum blocks (QLBs), QLB type II vs QLB type III, in caesarean delivery: A randomised study

Abstract: Interfascial plane blocks are very common regional anaesthesia techniques used for postoperative analgesia, and they have become highly diversified with the development of ultrasonography technologies and the introduction of this technology into anaesthesia practice. 1 The best known and first described techniques are the transversus abdominis plane (TAP) block and the ilioinguinal-iliohypogastric (II-IH) block. The efficacy of these blocks has been investigated in lower abdominal surgeries, such as caesarean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Surgical treatment is mainly used in clinic at the present stage [ 9 , 10 ]. In order to relieve the pain of patients during and after surgery, general anesthesia combined with QLB block or TAPB block is performed during and after surgery, which has a significant effect on relieving the pain of patients [ 11 , 12 ]. The mechanism of TAPB is to inject local anesthetic into the nerve fascia layer between the internal oblique muscle and transverse abdominis muscle to block relevant nerve sensory conduction so as to weaken the pain sensation in the skin, muscle, and parietal peritoneum of the anterior abdomen and achieve good abdominal analgesia [ 13 , 14 ].…”
Section: Related Workmentioning
confidence: 99%
“…Surgical treatment is mainly used in clinic at the present stage [ 9 , 10 ]. In order to relieve the pain of patients during and after surgery, general anesthesia combined with QLB block or TAPB block is performed during and after surgery, which has a significant effect on relieving the pain of patients [ 11 , 12 ]. The mechanism of TAPB is to inject local anesthetic into the nerve fascia layer between the internal oblique muscle and transverse abdominis muscle to block relevant nerve sensory conduction so as to weaken the pain sensation in the skin, muscle, and parietal peritoneum of the anterior abdomen and achieve good abdominal analgesia [ 13 , 14 ].…”
Section: Related Workmentioning
confidence: 99%
“…Kang et al demonstrated that the analgesia provided by QLB-II and QLB-III was comparable, and that the combination of QLB II and III is superior to either of the approaches alone (29) . Koksal et al demonstrated that QLB-III is superior to QLB-II (30) .…”
Section: Discussionmentioning
confidence: 99%
“…One small-sample-size study reported that the analgesic effect of QLB3 was a superior to that of QLB2 in cesarean delivery. 29 However, Brixel, et al 30 recently reported that 30 mL of the QLB2 solution could reach multiple locations around the quadratus lumborum muscle when sonographic localization was used. Therefore, future studies should consider investigating the effects of the different approaches of QLB using varying dosages of the local anesthetic.…”
Section: Discussionmentioning
confidence: 99%